Haemostatic Nanoparticles-Derived Bioactivity of from Selaginella tamariscina Carbonisata - Zhao, Yusheng; Zhang, Yue; Kong, Hui; Zhang, Meiling; Cheng, Jinjun; Luo, Juan; Zhao, Yan; Qu, Huihua (Molecules (Basel, Switzerland), 2020)
High-temperature carbonisation is used to prepare many traditional Chinese medicine charcoal drugs, but the bioactive haemostatic substances of these medicines and their mechanisms are still unknown. This study developed and evaluated nanoparticles (NPs) derived from Selaginella pulvinate Carbonisata (STC) for the first time. The haemostatic effect of STC-NPs prepared at 300, 350, and 400 °C were investigated in mouse tail amputation and liver scratch experiments. STC-NPs obtained at 400 °C had the strongest haemostatic effect, and were accordingly characterised by ultraviolet–visible spectroscopy, fluorescence spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, high resolution transmission electron microscopy, X-ray diffractometry, and X-ray photoelectron spectroscopy. STC-NPs averaged 1.4–2.8 nm and exhibited a quantum yield of 6.06% at a maximum excitation wavelength of 332 nm and emission at 432 nm. STC-NPs displayed low toxicity against mouse monocyte macrophage RAW 264.7 cells by CCK-8 assay, and STC-NP treatment significantly shortened bleeding time in rat and mouse models. Coagulation assays showed that the haemostatic effects of STC-NPs were related to improving the fibrinogen and platelet contents, as well as decreasing the prothrombin time that resulted from stimulating extrinsic blood coagulation and activating the fibrinogen system. The STC-NPs had remarkable haemostatic effects in the tail amputation and liver scratch models; these effects may be associated with the exogenous coagulation pathway and activation of the brinogen system, according to the evaluation of the mouse coagulation parameters. This novel evaluation supports the material basis of STC use in traditional Chinese medicine, and this article is worthy of study by authors of clinical pharmacy.